Impact of Practical Applications on Undergraduate English Language Instruction - Majumder, Rajib (International Journal of Applied and Scientific Research, 2024)
This article aims to share insights into the challenges faced by learners in acquiring English language skills at various stages of their academic journey, spanning from the early school years to the Undergraduate level. Drawing on two decades of teaching experience, particularly with students from rural areas in Andhra Pradesh, the author highlights difficulties encountered and proposes potential solutions. The article emphasizes the importance of incorporating practical applications in English language instruction at the Undergraduate level to debunk the misconception that learning English is insurmountable, even for those raised in challenging environments. The goal is to convey that English proficiency can be achieved comfortably, fostering a more inclusive and accessible approach to language education.